Caregiver Report of Executive Functioning in Adolescent Females With Anorexia Nervosa or Autism Spectrum Disorder - Timko, C. Alix; Herrington, John D.; Bhattacharya, Anushua; Kuschner, Emily S.; Yerys, Benjamin E. (Frontiers in Psychology, 2021)
Current literature suggesting a shared endophenotype between individuals with Anorexia Nervosa (AN) and Autism Spectrum Disorder (ASD) related to executive functioning (EF) has several limitations: performance-based instead of ecologically valid measures of set-shifting are used, lack of comparisons between same sex groups, and reliance on adult samples only. This was the first study directly comparing female youth with ASD to female youth with AN using an ecologically-valid measure of EF. A secondary data analysis combined caregiver reported EF on the Behavior Rating Inventory of Executive Functioning (BRIEF) for 22 female adolescent youth with AN and 29 female adolescent youth with ASD. EF in each group was compared to population norms and EF was compared between groups. Compared to population norms, adolescents with AN had elevated scores on Shift, Initiate, and Emotional Control scales and adolescents with ASD had elevated scores on all scales of the BRIEF and were more likely to have scores in the clinical range. There were significant differences between groups on all but three scales. The cognitive profiles and clinical scores of AN females were not comparable to that of ASD females. Findings reveal clear clinical impairment in females with ASD but not in females with AN. Results do not support hypothesis of similar real-world EF profiles between these groups. Results encourage further exploration into the similarities and distinctions between these two disorders.